Analysis of human papillomavirus infection and its correlation with cervical lesions in Huizhou women - Xiaoting Wang; Zengrui Ju; Qifei Lai; Qiaomei Liu; Lijie Gao; Jisheng Zhong (Scientific Reports)
Abstract To analyze the genotype distribution of human papillomavirus (HPV) infection in women in the Huizhou region of China and determine its correlation with age and degree of cervical lesions, with the aim to understand the characteristics of HPV infection in women in the region. A total of 65,127 patients who underwent HPV testing at the Second Maternal and Child Health Hospital of Huizhou City from January 2018 to December 2022 were selected as the research subjects. The polymerase chain reaction-reverse dot blot hybridization technique was used to detect HPV genotypes. The total detection rate of HPV infection was 7.25%, with single infection accounting for 70.94%. The detection rate of high-risk HPV was 6.73%. The top four high-risk types of HPV detected were 16, 52, 18, and 58. The distribution of HPV infection varied greatly among different age groups. The positive rates of HPV were the highest in the < 30-year-old group, followed by the ≥ 60-year-old group, showing a clear bimodal phenomenon. HPV infection in the population of Huizhou is mainly single infection and high-risk type, with higher infection rates in people < 30 and ≥ 60 years old. The local area should pay attention to the prevention and control of HPV.